2018
DOI: 10.11648/j.ijssam.20180302.13
|View full text |Cite
|
Sign up to set email alerts
|

A Survival Analysis of Invasive Breast Cancer Patients with and Without in Situ Neoplasm

Abstract: In situ neoplasm (or Carcinoma in situ (CIS)) is expression of malignant epithelial cells. This flat lesion is referred to as ductal carcinoma in situ (DCIS) and lobular carcinoma in situ (LCIS). Considering neoplasm leads one to an effectiveness survival analysis compared to the case that neoplasm is not attended. The objective of this research is to analyze statistically survival of invasive breast cancer patients considering 1) with in situ neoplasm, and 2) without in situ neoplasm, and providing a comparat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Our study found that marital status had no association with survival although, theoretically, patients who were married would get mental and financial support; thus, diagnosis and appropriate treatment would be performed earlier [27,28]. This theory justified by Hinyard et al [29] observed that unmarried women were 1.18 times (95% CI 1.15-1.20) more likely to be diagnosed at a later stage than married women across all AJCC stages.…”
Section: Discussionmentioning
confidence: 44%
“…Our study found that marital status had no association with survival although, theoretically, patients who were married would get mental and financial support; thus, diagnosis and appropriate treatment would be performed earlier [27,28]. This theory justified by Hinyard et al [29] observed that unmarried women were 1.18 times (95% CI 1.15-1.20) more likely to be diagnosed at a later stage than married women across all AJCC stages.…”
Section: Discussionmentioning
confidence: 44%